Analysis of return on asset (ROA) and return on equity (ROE) on profit growth in primary consumer goods sub-sector companies listed on the Indonesia stock exchange (Idx) For The 2021-2023 Period - Ratih Nur’aini; Indra Sulistiana (Enrichment : Journal of Management, 2026)
This study aims to investigate the effects of Return On Equity (ROE) and Return On Assets (ROA) on Profit Growth in the Indonesia Stock Exchange (IDX)-listed Primary Consumer Goods Sub-Sector Industry for the 2021–2023 Period. The background of this study is based on the importance of profitability performance as the main indicator of a company's financial health, especially in primary consumer goods companies that are relatively resilient to economic fluctuations and play a strategic role in meeting the community's basic needs. Several quantitative methods of linear regression analysis are used in this paper. The samples are chosen by the use of purposeful sampling. The company's annual financial statements provided secondary data. SPSS 27 was used to evaluate up to 72 pieces of data from 24 issuers during a three-year period. The results of the study show that ROA has minimal effect on profit growth, however ROE significantly impedes it. Concurrently, ROA and ROE have a major influence on profit growth for industrial companies in the main consumer goods subsector listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 timeframe